Sperm Quality Improvement in Male Cyprinids under Hormonal Induction - Abdelkader Rouabah (Indian Journal of Veterinary Anatomy, 2022)
This work was carried out on artificial reproduction of the species of fresh water (koi carp) by a hormonal induction in males and females with the main objective to improve the techniques of conservation of sperm quality. Similarly, the sutdy aimed to evaluate maximum storage at a refrigeration temperature of +4°C. The experiment was carried out at an aquaculture farm in Cheraga, Algeria. In the study, 14 broodstock (7 females and 7 males) were used. Pituitary and GnRH doses were determined according to the weight of each parent. The harvesting of the milt was done in the same way as the stripping of the females except that the milt was removed directly into syringes to be evaluated later. The results obtained showed that the sperm concentration of koi carp was of 4 to 30 x 109 spermatozoa/mL. This concentration had no relation to the volume of the milt, and it is for this reason that in artificial reproduction it is a very common practice to mix the milt of different males so that the success of fertilization is high. For both koi carp samples (with different dose of pituitary gland), sperm motility was over 75% during the first two days and then began to decrease to 15% on day 7. Vitality is related to motility, it was 85% for each sample. The duration of mobility decreases as a function of time (days). In the future, we suggest that further research on innovative sperm cryopreservation techniques has to be developed in order to extend its storage and lifespan.